Effects of Lactobacillus (Acidophilus) on Cutaneous Wound Repair with Respect to Neutrophil Count in Comparison with Steroid (Medical Forum Monthly, 2024)
Objective: To evaluate the effects of lactobacillus (acidophilus) in repairing of wound with respect to neutrophil count in comparison with steroid therapy.Study Design: Experimental studyPlace and Duration of Study: This study was conducted in the Department of Anatomy of Al-Tibri Medical College Isra University Karachi Campus from June 2014 to October 2014.Materials and Methods: Randomly selected Wistar albino rats were taken and their weight was between 100 – 150 gms. The rats were divided in three groups on the basis of topical application. Group I was treated with topical normal saline, Group II with topical lactobacillus(acidophilus), and Group III topical Steroid were applied once daily).Each group is further divided into four sub groups according to the day of sampling like group Ia (day 03), group Ib (day 07), group Ic (day 14) and group Id (day 21). Samples were taken on day 3,7,14 & 21 from each group and tissues were processed and stained to observe the neutrophil count that showed rapid healing processes. Data was analyzed on SPSS version 21 by applying ANOVA and post hoc tukey’s test.Results: Results compared the neutrophil count of Lactobacillus group with steroid group and control group. Mean ± SD of numbers of Neutrophils / x400 in group IIa was20.500 ± 0.577, in group IIb11.250 ± 1.258, in group IIc5.7500 ±.0.5000, group IId3.7500 ± 0.9574and in groupIawas54.25 ± 2.872, group Ib41.250 ± 2.629, group Ic23.500 ± 3.000 and group Id18.750 ± 0.957. The significant value was in group IIa and group Ia(P<0.000), group IIb and group Ib(P<0.000), group IIc and group Ic (P<0.000) and group IId and group Id (P<0.000). Mean ± SD of numbers of Neutrophils / x400 in groups IIa was 20.500 ± 0.577, in group IIb 11.250 ± 1.258, in group IIc 5.7500 ±.0.5000, group IId 3.7500 ± 0.9574 and group IIIa was54.500 ± 1.290, group IIIb 42.000 ± 1.414, group IIIc32.000 ± 0.8165 and group IIId28.750 ± 1.258. The significant value was in group IIa and group IIIa (P<1.000), group IIb and group IIIb (P<0.002), group IIc and group IIIc (P<0.000) and group IId and group IIId (P<0.000).Conclusion: Lactobacillus showed potent anti-inflammatory effect against both therapeutic groups.